A detailed experimental modal analysis of a clamped circular plate - Matthews, D.; Sun, H.; Saltmarsh, K.; Wilkes, Daniel; Munyard, A.; Pan, J. (Australian Acoustical Society, 2014)
A detailed study has been made of the natural frequencies and modal shapes of a thin steel discthat is clamped at the edges by two steel flanges. The aim was to determine how accuratelynumerical modeling could be used to predict the results and to investigate the possibility of any newexperimental observations even for this simple structure. A mechanical shaker and impact hammerwere used to excite the plate to obtain the frequency response function of the structure. The firsteight modal shapes at each of the resonant frequencies were then measured using laser scanningvibrometry. These results were compared with theoretical results obtained analytically andnumerically using PAFEC. While part of the existing understanding of the plate vibration wasconfirmed, significant differences were found in the values of the modal frequencies. Theexperimental data also demonstrated a dependence of the mode shape orientations and splitting ofdegenerated natural frequencies on the shaker position and properties of the flanges. This paperwill report on some interesting effects that need to be considered when doing such measurements and illustrate the risks of using numerical modeling without the use of experimental comparison.